2018
DOI: 10.1038/s41598-018-34648-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiovascular Magnetic Resonance Imaging on Identifying the Etiology of Cardiomyopathy in Patients Undergoing Cardiac Transplantation

Abstract: Errors in identifying the etiology of cardiomyopathy have been described in patients undergoing cardiac transplantation. There are increasing data that cardiovascular magnetic resonance imaging (CMR) provides unique diagnostic information in heart failure. We investigated the association of the performance of CMR prior to cardiac transplantation with rates of errors in identifying the etiology of cardiomyopathy. We compared pre-transplantation clinical diagnoses with post-transplantation pathology diagnoses ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
3
5
2
Order By: Relevance
“…In our study, the rate of misdiagnosis in patients undergoing both cardiac MRI and EMB were similar to those without undergoing both investigations. These findings were in contrast to the study by Lin et al [ 7 ]. They found that performance of cardiac MRI was significantly associated with fewer errors in pre-transplant/clinical diagnosis in patients with NISCM [ 7 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our study, the rate of misdiagnosis in patients undergoing both cardiac MRI and EMB were similar to those without undergoing both investigations. These findings were in contrast to the study by Lin et al [ 7 ]. They found that performance of cardiac MRI was significantly associated with fewer errors in pre-transplant/clinical diagnosis in patients with NISCM [ 7 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were in contrast to the study by Lin et al [ 7 ]. They found that performance of cardiac MRI was significantly associated with fewer errors in pre-transplant/clinical diagnosis in patients with NISCM [ 7 ]. The possible explanation of the difference between the studies remained unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Cardiac fibrosis is typically observed in 40–60% of DCM patients 3 , 4 . Broadly, two types of fibrosis have been identified.…”
Section: Introductionmentioning
confidence: 99%